Promoting Social and Human Resources for the Socio-Economic Development of the Northwest of Vietnam - Van Khanh, Nguyen (VNU Journal of Science: Policy and Management Studies, 2024)
Social and human resources refer to a wide range of factors related to people and culture that are crucial for a nation's or region's sustainable development. These resources help improve people's quality of life and lay the groundwork for economic and social growth. When developed and utilized effectively, they can promote economic growth while ensuring societal fairness. In the age of the Fourth Industrial Revolution and globalization, it is more important than ever to invest in social and human resources. To fully tap into the potential of people and their cultural values, countries must create suitable policies. This includes improving education, preserving and promoting national culture, and fostering creativity within local communities and ethnic groups. The Northwest region of Vietnam is significant for economic and social development as well as national security. This article examines the role of social and human resources, discusses how they can be mobilized, and identifies the challenges in utilizing this valuable resource to support economic and social development in the Northwest region during this period of national progress.